VALERIANA JATAMANSI: AN ETHNOBOTANICAL REVIEW - Patan, Afroz (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The main objective of review is an effort to give detailed information on Valeriana jatamansi and its multiple medicinal properties. Methods: As per the literature, the plant V. jatamansi is a perennial herb and found at subtemperate Himalayan regions of the Kumaon and Garhwal. The plant most popularly known as Valerian.â€ The plant belongs to the family Valerianaceae. The roots and rhizomes of the plants are traditionally used to treat ulcers, jaundice, dry cough, seminal weakness, skin diseases, leprosy, and for sleep enhancement due to the presence of a variety of different chemical constituents such as sesquiterpenes, coumarins, iridoids, lignanoids, alkaloids, and flavonoids. From literature, the reported methods performed for different pharmacological activities have been thoroughly discussed and complied. Results: Most of the studies compiled from literature shown that V. jatamansi possess antimicrobial, antioxidant, anti-inflammatory, cytotoxic, anxiolytic, and neuroprotective activities. Conclusion: The review reveals that continuous research on this plant is needed to know the exact molecular mechanism and further elaborative studies can lead to develop safe therapeutic use in modern medicine.